Bisphosphonate Modulation of the Gene Expression of Different Markers Involved in Osteoblast Physiology: Possible Implications in Bisphosphonate-Related Osteonecrosis of the Jaw - Manzano-Moreno, Francisco Javier (Int J Med Sci, 2018)
The aim of the present study was to elucidate the role of osteoblasts in bisphosphonates-related osteonecrosis of the jaw (BRONJ). The specific objective was to evaluate the effect on osteoblasts of two nitrogen-containing BPs (zoledronate and alendronate) and one non-nitrogen-containing BP (clodronate) by analyzing modulations in their expression of genes essential for osteoblast physiology. Real-time polymerase chain reaction (RT-PCR) was used to study the effects of zoledronate, alendronate, and clodronate at doses of 10(-5), 10(-7), or 10(-9) M on the expression of Runx-2, OSX, ALP, OSC, OPG, RANKL, Col-I, BMP-2, BMP-7, TGF-β1, VEGF, TGF-βR1, TGF-βR2, and TGF-βR3 by primary human osteoblasts (HOBs) and MG-63 osteosarcoma cells. Expression of these markers was found to be dose-dependent, with no substantive differences between these cell lines. In general, results demonstrated a significant increase in TFG-β1, TGF-βR1, TGF-βR2, TGF-βR3, and VEGF expressions and a significant reduction in RUNX-2, Col-1, OSX, OSC, BMP-2, BMP-7, ALP, and RANKL expressions, while OPG expression varied according to the dose and cell line. The results of this in vitro study of HOBS and MG-63 cell lines indicate that low BP doses can significantly affect the expression of genes essential for osteoblast growth and differentiation and of genes involved in regulating osteoblast-osteoclast interaction, possibly by increasing TGF-β1 production. These findings suggest that osteoblasts may play an important role in BRONJ development, without ruling out other factors.